Effectiveness of Using ALEKS to Provide Personalized Guidance According to the Needs and Abilities of High School Students: Teacher Perspectives - Alifah, Sabrina; Pratama, Andika Putra; Wahyunengsih (MAXIMA : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the effectiveness of using ALEKS in providing personalized guidance according to the needs and abilities of high school students from teachers' perspectives. The research employs a quantitative descriptive method, with data collected through questionnaires with teachers’ who have used ALEKS in their teaching. That said, it’s not without its issues limited access to technology and the time it takes for teachers to get used to the system can be real hurdles. Still, ALEKS shows promise as a tool for personalizing learning, though schools may need to provide more support to make the most of it. Keywords: ALEKS, personalized guidance, learning effectiveness, teachers' perspective, educational technology